2023
DOI: 10.4018/ijea.316173
|View full text |Cite
|
Sign up to set email alerts
|

Age in the Acceptance of Mobile Social Media

Abstract: This paper focuses on determining the age-based differences among consumers in terms of the acceptance of mobile social media. In doing so, the younger age group is represented by Generation Y and the elderly by Baby Boomers. Further, the famous UTAUT2 model is applied, and relationships mentioned in it are evaluated for the two age groups. For this purpose, a sample of 249 respondents was obtained from the online survey conducted in the state of Punjab in India. The statistical technique of multi-group path a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…The Boomer generation has strong interpersonal communication and leadership skills. However, the work challenges of this generation are related to adapting to new technologies, as they tend to acquire them more slowly [30]. They require more time to assimilate technological additions and collaborate in the learning process.…”
Section: The Baby Boomersmentioning
confidence: 99%
“…The Boomer generation has strong interpersonal communication and leadership skills. However, the work challenges of this generation are related to adapting to new technologies, as they tend to acquire them more slowly [30]. They require more time to assimilate technological additions and collaborate in the learning process.…”
Section: The Baby Boomersmentioning
confidence: 99%
“…Millennial and Social Websites: Research conducted (Ukpabi et al, 2021) revealed that employees in younger and older age groups have different levels of acceptance of certain technological factors. Businesses may use these distinctions to plan effective social website campaigns and create branding plans that are appropriate for various generation (Vasudeva, 2023). Research on usage of social websites by millennials, revealed how it affects their lifestyles and social behaviours.…”
Section: Literature Reviewmentioning
confidence: 99%